A method to determine pore compressibility based on permeability measurements. (December 2015) - Ling, Kegang; He, Jun; Pei, Peng; Ge, Jun; Ni, Xiao
Highlights: A method using permeability measurement to determine pore compressibility was proposed. The method is reliable to estimate pore compressibility. The proposed method is time saving and cost efficient.